ASET TETAP - M. Setiadi Hartoko (JURNAL AKUNTANSI, EKONOMI dan MANAJEMEN BISNIS, 2017)
A current asset is a company asset that has a useful life of less than one year while fixed assets are assets of companies that have a useful life of more than one year. The research was conducted by analyzing, bibliographic data and question and answer to the officials related to the discontinuation of the use of fixed assets at PT IFCA Property365 Indonesia is done in two ways, that is by way of sale and eliminated / destroyed.serta accounting records in accordance with the rules of Indonesia financial accounting standards (PSAK).